2016
DOI: 10.2147/rrbs.s63402
|View full text |Cite
|
Sign up to set email alerts
|

Marine biosecurity: protecting indigenous marine species

Abstract: Nonindigenous species (NIS) are those that have been intentionally or unintentionally introduced outside of their native range as a consequence of human activity. If these species then threaten indigenous species and biodiversity, and/or cause economic damage, they are referred to as "invasive." Biological invasions are not only one of the greatest threats to indigenous marine biodiversity, but they can also cause massive economic and ecological damage. Their presence could also lead to a water body failing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…The development of marinas constitutes a significant change to the near-shore environment (Rivero et al 2013 ) and results in a site with high potential for increased establishment of NNS. The high prevalence of NNS found within marinas suggests that incorporating biosecurity measures into marina design and operation might greatly reduce secondary spread of NNS by the recreational sailing sector (Cook et al 2016 ). While there may be some associated costs with changes to project development processes and operation, over 40 % of sailors questioned indicated that they would preferentially use marinas which offered increased biosecurity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of marinas constitutes a significant change to the near-shore environment (Rivero et al 2013 ) and results in a site with high potential for increased establishment of NNS. The high prevalence of NNS found within marinas suggests that incorporating biosecurity measures into marina design and operation might greatly reduce secondary spread of NNS by the recreational sailing sector (Cook et al 2016 ). While there may be some associated costs with changes to project development processes and operation, over 40 % of sailors questioned indicated that they would preferentially use marinas which offered increased biosecurity.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive NNS can cause significant economic and social impacts and are estimated to cause global damage amounting to $120 billion annually (Pimentel et al 2005 ). Biosecurity measures including quarantine, customs and legislative controls have long been in place for terrestrial pest species (Cook et al 2016 ). During the last decade, marine invasive NNS have received increased attention from both scientists and policy makers (Genovesi et al 2014 ; Hulme 2009 , 2015 ); yet both ecological knowledge and biosecurity practices to address marine invasive NNS still lag behind those of terrestrial species (Williams and Grosholz 2008 ; Cook et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Human-mediated introduction of marine species to a region outside their natural range of distribution is widely considered to be the major threat to indigenous species diversity and community structures. This can cause habitat modifications, changes in ecosystem functioning, introduction of new diseases and parasites, and genetic modifications, such as hybridization with the native taxa (Cook et al, 2016). NIS, and especially marine IAS, have an overall impact on the provisioning, regulating, cultural, and supporting ecosystem services (Kettunen et al, 2008).…”
Section: Impact Of Non-indigenous Speciesmentioning
confidence: 99%
“…Recent research involving the identification and assessment of the risks associated with an activity or event with respect to the introduction of non-native species [58,59] may inform biosecurity planning for the MRE industry. Additional research has also been undertaken identifying the transfer pathways of non-native species that occur in the MRE industry [32,55].…”
Section: Invasive Species Risk and Biosecuritymentioning
confidence: 99%